Avaliação do comportamento higrotérmico de concretos produzidos com resíduos de borracha de pneu e poliestireno expandido para aplicação em paredes de concreto - Alves, Camila dos Reis (2020)
The concrete wall construction system was widely used, standing out among the construction solutions adopted in social housing. However, when it comes to thermal performance of these system, it's verified that the construction system, as it's being implemented, isn't suitable for all Brazilian bioclimatic zones. Therefore, this research produced a concrete of reference (0% replacement) and concretes with partial replacement of natural small aggregates by tire rubber (12.5% and 15% by volume) and natural large aggregates by recycled and crushed expanded polystyrene (EPS) (60% and 70% by volume), in order to evaluate the hygrothermal behavior of these alternative materials for application on concrete walls. The mechanical and hygrothermal properties of these materials were analyzed. The mechanical properties were evaluated by means of compressive and tensile tests. The transport of moisture, liquid water and water vapor, was characterized by absorption tests, desorption isotherms, permeability to water vapor and drying of concretes. The heat transfer was studied by means of thermal conductivity and thermal testing with concrete plates exposed to solar radiation. In a second step, the hygrothermal properties of the concretes were used as input data in hygrothermal simulation considering the construction system of concrete walls. The results obtained showed that the concretes with residues, tire rubber and EPS, are more porous than the reference, have different absorption characteristics, are more permeable to water vapor, behave differently in drying and have less thermal conductivity. However, through the results of the hygrothermal simulation, it was possible to conclude that the concretes with residues, although presenting different hygrothermal properties, behave similarly when applied to the construction system.